Semantic preference, prosody and distribution of synonymous adjectives in COCA - Selmistraitis, Linas (Penerbit Universiti Kebangsaan Malaysia, 2020)
Synonymous word pairs often become an obstacle on the road to favourable result in composing academic texts because semantic prosody and semantic preference of these words are neglected. The current study examined the concordance lines with synonymous adjectives succinct & concise, coherent & cohesive, precise & accurate in the academic texts of Corpus of Contemporary American English (COCA) and identified semantics of co-occurring collocates, interchangeability of synonyms and their distribution across nine academic disciplines. The research describes the semantic arrangement of collocations with synonymous pairs of words and encourages persons with academic pursuits rely on corpus data based tools to improve knowledge of semantic prosody and preference of words with similar meanings. The study showed that near synonyms succinct & concise, coherent & cohesive, precise & accurate have different semantic preference and distribution across registers which should be taken into consideration while building collocations with these words. However, semantic prosody tendencies of these synonyms are similar. The analysed synonyms cannot be used interchangeably in all contexts. They are also unevenly scattered across registers. The current study will help to improve learning, teaching, and research of English academic vocabulary in its many contexts.